Is cryptocurrency technology adoption effective in individuals? Investment behavior - AKGÜL, ŞEVKET IŞIL (My University, 2023)
Behavioral intentions of individuals occur as a result of positive or negative evaluations of any object or idea. It is a determinant that has a significant impact on transforming an individual\"s ideas into behavior. The structure and effectiveness of information in financial markets are vital to understanding the behavior of investors, because the digital economy that develops with crypto money is psychologically significantly different from the cash economy. Accordingly, this study examined the main intentions or motivational factors that persuade individuals to invest in cryptocurrencies and the way these factors affect the actual investment behavior. This was done in the context of behavioral considerations in finance through the Unified Technology Acceptance Model (UTAUT). As a result of the model estimation, it has been concluded that the performance expectation is an important factor behind the investment behavior, and its effect changes considering positive or negative news about the pricing of cryptocurrencies.
Keywords: Sosyal ve Beşeri Bilimler; Çalışma Ekonomisi ve Endüstri ilişkileri; Yönetim ve Çalışma Psikolojisi; Social Sciences and Humanities; Labor Economics and Industrial Relations; Management and Industrial Psychology; YÖNETİM; Ekonomi ve İş; Sosyal Bilimler (SOC); MANAGEMENT; ECONOMICS & BUSINESS; Social Sciences (SOC); Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Social Sciences & Humanities; cryptocurrency technology; investment behavior; UTAUT model; ACCEPTANCE MODEL 3; INFORMATION-TECHNOLOGY; USER ACCEPTANCE; INTENTION; ECONOMICS; CONSUMERS